Growth, Competition, and Efficiency towards Net-Profit-and-Loss Sharing Margin: Study of Indonesian Islamic Microfinance Institutions - Pratama, Bima Cinintya; Innayah, Maulida Nurul (Universitas Islam Indonesia, 2019)
For past years, many critics has been faced on Microfinance institutions (MFIs) facing because of their tendency of taking high margin. Therefore, it is important to understand the factors that affect margin in microfinance industry. This study examines the effect of MFIs growth, competition, and efficiency on the margin. The data collected from Otoritas Jasa Keuangan (OJK) database from 2011-2016 and conducted on Indonesian Islamic MFIs. The final sample used in this study consists of a total of 2160 observations. This study uses panel data regression model analysis to analyze the obtained data. The results obtained from this study showed that Net-profit-and-loss sharing margins (NPLS) are able to be explained by MFIs growth and efficiency but not with HHI, which is the proxy of the degree of competition.